Ta co B>1
=>A=20^10+1'20^10-1<20^10+1/2010-3+1
=>A<20^10+1/20^10-3+1
=>A<20^10-1/20^10-3
=>A<B
Vậy A<B
Ta co B>1
=>A=20^10+1'20^10-1<20^10+1/2010-3+1
=>A<20^10+1/20^10-3+1
=>A<20^10-1/20^10-3
=>A<B
Vậy A<B
So sánh : \(A =\frac{20^{10} +1}{20^{10}-1} ; B =\frac{20^{10} -1}{20^{10} -3}\)
so sánh \(A=\frac{20^{10}+1}{20^{10}-1};B=\frac{20^{10}-1}{20^{10}-3}\)
So sánh A và B:
\(A=\frac{20^{10}+1}{20^{10}-1};B=\frac{20^{10}-1}{20^{10}-3}\)
So sánh A=\(\frac{20^{10}+1}{20^{10}-1}\)và B=\(\frac{20^{10}-1}{20^{10}-3}\)
So sánh : A=\(\frac{20^{10}+1}{20^{10}-1}\)và B=\(\frac{20^{10}-1}{20^{10}-3}\)
So Sánh \(A=\frac{20^{10}+1}{20^{10}-1}\text{và }B=\frac{20^{10}-1}{20^{10}-3}\)
so sánh A= \(\frac{20^{10}+1}{20^{10}-1}\)va B= \(\frac{20^{10}-1}{20^{10}-3}\)
So sánh A và B
A = \(\frac{20^{10}+1}{20^{10}-1}\)Và B = \(\frac{20^{10}-1}{20^{10}-3}\)
so sánh\(A=\frac{20^{10}+1}{20^{10}-1}vàB=\frac{20^{10}-1}{20^{10}-3}\)